2020
DOI: 10.14776/piv.2020.27.e12
|View full text |Cite
|
Sign up to set email alerts
|

Human Parechovirus: an Emerging Cause of Sepsis-Like Syndrome in Infants Aged under 3 Months

Abstract: Purpose: This study aimed to investigate the clinical characteristics of human parechovirus (HPeV) infection in sepsis-like syndrome in infants aged under 3 months. Methods: Medical records of infants aged under 3 months with sepsis-like symptoms who were admitted between July 1, 2018 and August 31, 2018 were reviewed. A multiplex reverse transcription-polymerase chain reaction panel test was performed on the cerebrospinal fluid (CSF). Thirty-nine enrolled infants were categorized into three groups: 11 in grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 24 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…Almost all reports showed that the youngest (under 3 months of age and in particular neonates) were the most affected patients. [ 9 12 , 14 , 21 , 23 , 26 28 , 32 , 33 , 59 62 , 64 68 , 70 ]. Of note, an exceptional adolescent onset was reported in an immunosuppressed 17-year-old girl [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Almost all reports showed that the youngest (under 3 months of age and in particular neonates) were the most affected patients. [ 9 12 , 14 , 21 , 23 , 26 28 , 32 , 33 , 59 62 , 64 68 , 70 ]. Of note, an exceptional adolescent onset was reported in an immunosuppressed 17-year-old girl [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fever was the most frequent presenting sign [ 1 , 41 , 44 – 47 , 49 , 50 , 52 – 58 ]. In fact, fever occurrence ranged between 80% and 100% [ 8 , 10 – 12 , 14 , 17 , 21 , 23 , 25 28 , 32 , 33 , 60 64 , 69 , 70 ]. However, in an American retrospective study, 2% of patients reported hypothermia (TC < 35 °C) instead of hyperthermia [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations